Modified Oxford Bone Scores Are Reduced in Patients With Slipped Capital Femoral Epiphysis Compared With Healthy Controls. Issue 8 (September 2021) - Pflug, Emily M.; Herrero, Christina; Zhong, Jack R.; Castañeda, Pablo
Abstract : Background: The etiology and pathogenesis of slipped capital femoral epiphysis (SCFE) are attributable to abnormalities of the proximal femoral epiphysis. This study aimed to examine if there is a difference in the bone age of patients diagnosed with SCFE compared with patients without hip pathology. Methods: We identified a consecutive series of patients treated for SCFE between December 2012 and December 2019 from a departmental database. Retrospective chart review was performed to collect demographic information and patient medical history. We then obtained a control group of statistically similar patients based on age and sex. These patients did not have hip pathology or medical comorbidities that could alter their bone age. The modified Oxford bone score (mOBS) was calculated for both groups by 3 blinded reviewers. We excluded patients with unstable slips, endocrine disorders, and inadequate imaging. Results: We identified 60 patients with stable idiopathic SCFE during the study period; 45 met inclusion criteria and were included in the final analysis. There were 27 males and 18 females. The average age of patients with SCFE was higher in males than females (12.6 vs. 11.1, P <0.01). Patients in the comparison cohort did not differ significantly from the SCFE cohort in terms of age (11.6 vs. 12.0, P =0.06) or sex ( P =0.52). The comparison group's median mOBS was significantly higher than the SCFE group (22.5 vs. 20.5, P <0.01). The difference in the mOBS between male and female patients in the SCFE group approached significance (20.0 vs. 21.0, P =0.05). The weighted κ coefficient was 0.93. Conclusions: Patients with SCFE have a decreased bone age compared with patients without hip pathology. Male patients with SCFE were more likely to be older compared with female patients. Level of Evidence: Level IV—retrospective study.